Diseño de una planta de tratamiento de agua con funcionalidad móvil para mares y océanos contaminados por derrames de tipo oleoso. (2024)
This document presents the partial conceptual design of a water treatment plant whose construction is intended inside a ship, with the objective of originating the idea of ​​a comprehensive tool for cleaning some types of oil spills in seas and oceans; The design is intended to be scalable to cover different bodies of water in the future. A plant design consists of 12 documents, but in order to guarantee the transmission of the idea, 6 keys were developed: design philosophy, process design using PFD diagram, plant design using P&ID diagram, a brief description of the functional design , equipment layout sketches, and a simplified financial feasibility analysis to evaluate feasibility.